2012
DOI: 10.1684/epd.2012.0483
|View full text |Cite
|
Sign up to set email alerts
|

Starting at the beginning: the neuropsychological status of children with new‐onset epilepsies*

Abstract: This review examines the neurodevelopmental contributions to the cognitive and behavioral complications of epilepsy. Following a brief review of the lifespan complications of childhood epilepsies, attention turns to cognitive, psychiatric and social correlates of childhood epilepsies reported in population-based and tertiary care studies. The focus then becomes the neurobehavioral status of children with new onset epilepsy—a point in time not confounded by the effects of years of recurrent seizures, medication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 96 publications
1
46
0
2
Order By: Relevance
“…Therefore, the elevated rate of impaired EF in our group suggests that biophysiological dysfunctions affect cognitive performance in an early phase of epilepsy. Several studies suggest that cognitive impairment even antecedes the first seizure [17,18]. The specificity of the deficits regarding EF remains to be a subject of future studies.…”
Section: Cognitive Dysfunction In Children With New-onset Epilepsy Prmentioning
confidence: 97%
See 2 more Smart Citations
“…Therefore, the elevated rate of impaired EF in our group suggests that biophysiological dysfunctions affect cognitive performance in an early phase of epilepsy. Several studies suggest that cognitive impairment even antecedes the first seizure [17,18]. The specificity of the deficits regarding EF remains to be a subject of future studies.…”
Section: Cognitive Dysfunction In Children With New-onset Epilepsy Prmentioning
confidence: 97%
“…Further, there is ongoing research on potential effects of specific drug substances on cognitive performance [14]. To date, several studies focused on pediatric populations [12,[15][16][17], but there is a significant need for investigating the cognitive profile of children with new-onset epilepsy prior to initiation of drug treatment to control for the potential effect of Epilepsy & Behavior 60 (2016) 42-49 medication [18]. Additionally, recent studies point to a heightened prevalence of cognitive deficits in adults as well as in children with newonset epilepsy in the early phase of illness, i.e., before treatment is started or even prior to seizures [4,11,[19][20][21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to proximal effects within the temporal lobe, recent work has established that the structural and functional effects of TLE can extend well beyond the region of seizure onset [75][76][77][78][79]. Diffusion tensor imaging studies have shown that fiber tracts connecting the temporal lobe with other brain regions are frequently adversely affected in patients with TLE; reduced integrity of the arcuate fasciculus in particular is associated with poor object-naming performance [50].…”
Section: Focal Effectsmentioning
confidence: 99%
“…However, several studies have reported the absence of such effects across these cognitive domains [27][28][29][30][31]. These inconsistencies not only may reflect differences in methodology and sample characteristics but also may be due to limitations of utilizing age at seizure onset as a marker of development, a variable enmeshed with illness duration, medication, and cumulative burden of seizures [32].…”
Section: Introductionmentioning
confidence: 99%